Characterization method of silicon element distribution in carbon fiber precursor and carbon filament

By burying carbon fibers in the resin and testing with nanoion probes, the problem that the prior art cannot effectively characterize the distribution of silicon elements in carbon fibers is solved, and the accurate characterization of the distribution of carbon fiber protofilament and carbon wire silicon elements is achieved, which improves the control accuracy of the manufacturing process.

CN119846005APending Publication Date: 2025-04-18INST OF CHEM CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311341746.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art cannot effectively characterize the distribution of silicon elements in carbon fibers, making it difficult to determine whether the oil agent penetrates into the original wire and the residual position of the silicon elements in the carbon wire.

Method used

By embedding the carbon fiber raw wire or carbon wire to be tested in the resin to be tested, and using a nanoion probe for testing, the Si/C value and silicon element distribution diagram of the carbon fiber raw wire or carbon wire are obtained, and the distribution of silicon elements are intuitively judged.

Benefits of technology

The accurate characterization of the distribution of carbon fiber proto-filament and carbon fiber silicon elements is achieved, and it can intuitively judge whether the oil agent penetrates into the interior of the raw wire and the residual position of the silicon element in the carbon fiber, which improves the control accuracy of the carbon fiber manufacturing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119846005A_ABST
    Figure CN119846005A_ABST
Patent Text Reader

Abstract

The invention discloses a characterization method of silicon element distribution in a carbon fiber precursor and a carbon filament. Comprising the following steps: 1) embedding a carbon fiber precursor or carbon filament to be tested in resin to prepare a test sample; and 2) after spraying metal on the test sample, testing by using a nano ion probe to obtain a Si / C value and a silicon element distribution diagram of the carbon fiber precursor or the carbon filament, and visually judging whether the oiling agent permeates into the precursor and whether an oil film formed by the oiling agent on the precursor is uniform according to the silicon element distribution diagram of the carbon fiber precursor. And directly judging the residual position of the silicon element in the carbon filament through the silicon element distribution diagram of the carbon filament. According to the invention, silicon element distribution characterization of the carbon fiber precursor and the carbon filament is realized. Whether the oiling agent permeates into the protofilament or not and whether an oil film formed by the oiling agent on the protofilament is uniform or not can be visually judged through the silicon element distribution diagram of the protofilament. And the residual position of the silicon element in the carbon filament can be intuitively judged through the silicon element distribution diagram of the carbon filament.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material testing, and in particular relates to a method for characterizing the distribution of silicon elements in carbon fiber precursors and carbon filaments. Background Art

[0002] The manufacturing of carbon fiber mainly includes the spinning process of polyacrylonitrile precursor, the pre-oxidation process (converted into pre-oxidized tow in an oxygen atmosphere of 200°C to 400°C) and the carbonization process (carbonized in an inactive atmosphere above 1000°C). In the above-mentioned pre-oxidation process and the initial carbonization process (the initial stage of the carbonization process), single fibers are prone to welding, causing fuzzing and wire breakage. In order to prevent welding between single fibers, a known method is to coat the surface of the precursor tow with a layer of heat-resistant oil film (oil treatment). In order to prepare high-performance carbon fibers, the oil film needs to withstand high temperatures above 200°C, so the main component of the oil film usually uses functional polysiloxane with excellent heat resistance. The oil film attachment method usually uses an emulsifier to emulsify the functional polysiloxane into an aqueous silicone emulsion, and then in the spinning process, the aqueous silicone emulsion is attached to the surface of the precursor tow through an oiling process. The heat-resistant oil film attached to the raw yarn can not only prevent the adhesion between the pre-oxidized yarn filaments and the carbon yarn filaments, and reduce the surface defects of the carbon fiber, but also reduce the friction between the fiber and the metal, help eliminate the static charge accumulated during the carbon fiber manufacturing process, increase the bonding between the fibers, and ensure the smooth progress of the carbon fiber manufacturing process.

[0003] In order to prepare high-performance carbon fiber, the oil should be avoided as much as possible from penetrating into the interior of the polyacrylonitrile precursor. The reason is that in the subsequent pre-oxidation and carbonization process, the oil that penetrates into the interior of the precursor is thermally degraded to form silicon dioxide or silicon carbide (i.e., ash), which remains inside the carbon fiber, hindering the bonding between carbon-carbon and unable to form a graphite structure, resulting in structural defects, resulting in reduced mechanical properties of the carbon fiber. In order to determine whether the oil has penetrated into the interior of the fiber and determine the residual position of the silicon element in the carbon fiber, it is necessary to quantitatively test the silicon element distribution of the carbon fiber precursor and the carbon fiber. The known prior art cannot achieve the characterization of the silicon element distribution of the carbon fiber. Prior art CN202210004348.2 uses an X-ray photoelectron spectrometer (XPS) (PHIVersaProbe III) to check the surface silicon content (S) of the carbon fiber. Then, the original sample is directly tested by ion etching (ion gunetching) to measure the inner layer silicon content (I) at a depth of 0.5 μm from the surface. The distribution of silicon in the carbon fiber is judged by the silicon impurity content ratio (I / S) of the inner and outer layers of the carbon fiber. Obviously, this indirect characterization method cannot test the actual carbon fiber silicon element distribution. Summary of the invention

[0004] The present invention aims to provide a characterization method for the silicon distribution of carbon fiber precursor and carbon filament, which can characterize the silicon distribution of the cross section of the carbon fiber precursor and carbon filament. Through the intuitive silicon distribution diagram, it is possible to accurately judge whether the oil agent has penetrated into the precursor, the uniformity of the oil agent attached to the fiber surface, and the residual position of the silicon element in the carbon filament.

[0005] The method for characterizing the silicon element distribution of carbon fiber precursor and carbon fiber provided by the present invention comprises the following steps:

[0006] 1) Embedding the carbon fiber precursor or carbon fiber to be tested in resin to prepare a test sample;

[0007] 2) After the test sample is sprayed with gold, it is tested using a nano-ion probe to obtain the Si / C value and silicon element distribution diagram of the carbon fiber precursor or carbon filament. The silicon element distribution diagram of the carbon fiber precursor can be used to visually judge whether the oil agent has penetrated into the precursor and whether the oil film formed by the oil agent on the precursor is uniform. The silicon element distribution diagram of the carbon filament can be used to visually judge the residual position of the silicon element in the carbon filament.

[0008] In step 1) of the above method, the resin has a Barcol hardness greater than 60 and no volatiles are released under high vacuum conditions;

[0009] In one embodiment of the present invention, the test sample is prepared by the following method: Araldite 506 resin, curing agent 1 of Araldite 506 resin and curing agent 2 of Araldite 506 resin are uniformly mixed, added into a mold, the carbon fiber precursor or carbon filament to be tested is vertically inserted into the resin mixture, cured, the resin embedded with the carbon fiber precursor or carbon filament to be tested is demolded, and the disc is obtained by low-temperature brittle fracture, grinding and polishing until the brittle fracture surface of the disc is close to a mirror surface, and the attachment is removed to obtain;

[0010] Wherein, the curing agent 1 of the Araldite 506 resin may specifically be 1,8-diamino-p-menthane;

[0011] The curing agent 2 of the Araldite 506 resin can specifically be 1-(2-aminoethyl)piperazine;

[0012] Araldite 506 resin, Araldite 506 resin curing agent 1, and Araldite 506 resin curing agent 2 are mixed in a mass ratio of 7.5:6-8:0-2;

[0013] The shape of the mold is cylindrical, and its diameter is 10-30 mm, specifically 10 mm;

[0014] The curing temperature is 40-50°C, specifically 45°C, and the curing time is 5-30h, specifically 24h;

[0015] The low-temperature brittle fracture is carried out in liquid nitrogen;

[0016] The disc has a thickness of 2-10 mm, specifically 4 mm, and a diameter of 10-30 mm;

[0017] The grinding and polishing is performed by grinding with sandpapers of different meshes, wherein the meshes of the sandpapers are preferably from low to high, and the preferred meshes are 200-400, 800-1500, 2500-3000, and 5000-8000, respectively. The material of the sandpaper is preferably diamond sandpaper.

[0018] In step 2), the conditions for the nano-ion probe test are: using O - The primary ion current has a beam spot diameter of about 50nm, an intensity of about 50pA, and an acceleration voltage of 16kV.

[0019] Since the content of silicon in carbon fiber precursor and carbon filament is low (about 500ppm to 2500ppm), the test instrument is required to have extremely high sensitivity; the diameter of carbon fiber precursor and carbon filament is at the micron level, the test instrument is required to have high spatial resolution. The sensitivity and spatial resolution of the ion probe cannot be used for silicon testing of carbon fiber precursor and carbon filament. The nano-ion probe has a primary beam spot size of less than 50 nanometers and can achieve trace-level sensitivity in the submicron region, which can meet the above test requirements and is therefore used as a test instrument.

[0020] The test sample of the nano-ion probe must meet the following conditions: 1) The sample is solid and non-volatile; 2) The sample surface is highly flat. The flatness of the sample surface has a significant impact on the measurement accuracy and precision. The sample is required to be made into a polished surface and reflective surface under a low-power reflective microscope. 3) The sample surface is conductive. If it is not conductive, it needs to be sprayed with gold film or carbon film. 4) The sample size is a circular sample target with a diameter of 9-10mm, 11.7-13.1mm or 24.4-25.7mm (thickness <4mm).

[0021] The present invention has the following beneficial effects:

[0022] According to the present invention, the silicon distribution characterization of carbon fiber precursor and carbon filament is achieved. Through the silicon distribution diagram of the precursor, it is possible to intuitively judge whether the oil agent has penetrated into the inside of the precursor and whether the oil film formed by the oil agent on the precursor is uniform. Through the silicon distribution diagram of the carbon filament, it is possible to intuitively judge the residual position of the silicon element in the carbon filament. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 (a) is an electron scanning photograph of the T700 precursor measured in Example 1 of the present invention; (b) is a silicon element distribution diagram of the T700 precursor measured in Example 1 of the present invention; (c) is the Si / C value at any straight line (yellow line segment) in the silicon element distribution diagram.

[0024] Figure 2(a) is an electron scanning photograph of the T700 carbon filament measured in Example 2 of the present invention; (b) is a silicon element distribution diagram of the T700 carbon filament measured in Example 2 of the present invention; (c) is the Si / C value at any straight line (yellow line segment) in the silicon element distribution diagram.

[0025] Figure 3 This is the silicon element distribution diagram of the T700 raw silk measured in Comparative Example 1 (DES scanning photo).

[0026] Figure 4 This is the silicon element distribution diagram of the T700 carbon filament measured in Comparative Example 2 (DES scanning photo). DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0028] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0029] Example 1

[0030] First, T700 carbon fiber precursor was embedded in resin. The resin was a mixture of three substances, namely (1) Araldite 506 resin, (2) 1,8-diamino-p-menthane, and (3) 1-(2-aminoethyl)piperazine. The three substances were evenly mixed in a mass ratio of (1): (2): (3) of 7.5:7:1, and added into a cylindrical polytetrafluoroethylene mold with a diameter of 10 mm. The T700 carbon fiber precursor was vertically inserted into the resin and cured at 45°C for 24 hours.

[0031] After the resin embedded with T700 carbon fiber precursor was demoulded, it was brittlely broken into a disc with a thickness of about 4 mm (diameter 10 mm) in liquid nitrogen at low temperature. One side of the disc was polished to a near mirror surface on a grinding and polishing machine (Biao Le MiniMet1000) using 360 mesh, 1500 mesh, 3000 mesh, and 8000 mesh diamond sandpaper (Rong HRTX) in sequence. The polished surface was blown off the attachments with an ear cleaning ball, and the nano-ion probe test (using O - The primary ion current, beam spot diameter is about 50nm, intensity is about 50pA, and acceleration voltage is 16kV).

[0032] The silicon distribution of T700 carbon fiber precursor is as follows Figure 1As shown, silicon is mainly distributed in the surface layer of the original silk about 1 micron, and a small amount of silicon is distributed linearly inside the original silk, proving that a small amount of oil penetrates from the surface of the original silk into the interior of the original silk.

[0033] Example 2

[0034] First, the T700 carbon fiber is embedded in a resin. The resin is a mixture of three substances, including (1) Araldite 506 resin, (2) 1,8-diamino-p-menthane, and (3) 1-(2-aminoethyl)piperazine. The three substances are evenly mixed in a mass ratio of (1): (2): (3) of 7.5:7:1, and added into a cylindrical polytetrafluoroethylene mold with a diameter of 10 mm. The T700 carbon fiber is vertically inserted into the resin and cured at 45°C for 24 hours.

[0035] After the resin embedded with T700 carbon fiber was demoulded, it was brittlely fractured into a disc with a thickness of about 4 mm (diameter 10 mm) in liquid nitrogen at low temperature. One side of the disc was polished to a near mirror surface using 360 mesh, 1500 mesh, 3000 mesh, and 8000 mesh diamond sandpaper (Rong HRTX) on a grinding and polishing machine (Biao Le MiniMet1000). The attached matter was blown off the polished surface with an ear-cleaning ball, and the nano-ion probe test (using O - The primary ion current, beam spot diameter is about 50nm, intensity is about 50pA, and acceleration voltage is 16kV).

[0036] The silicon element distribution of T700 carbon fiber is as follows Figure 2 As shown, silicon is mainly distributed in the surface layer of the carbon filament, about 1 micron; a small amount of silicon is distributed inside the carbon filament, proving that during the pre-oxidation and carbonization process, a small amount of silicon remains inside the carbon fiber.

[0037] Comparative Example 1

[0038] First, T700 carbon fiber precursor was embedded in resin. The resin was a mixture of three substances, including (1) Araldite 506 resin, (2) 1,8-diamino-p-menthane, and (3) 1-(2-aminoethyl)piperazine. The three substances were evenly mixed in a ratio of (1): (2): (3) of 7.5:7:1, and added into a cylindrical polytetrafluoroethylene mold with a diameter of 10 mm. The T700 carbon fiber precursor was vertically inserted into the resin and cured at 45°C for 24 hours.

[0039] After the resin embedded with T700 carbon fiber precursor was demolded, it was brittlely fractured into a disc with a thickness of about 4 mm (diameter 10 mm) at low temperature in liquid nitrogen. One side of the disc was polished to a near mirror surface using 360 mesh, 1500 mesh, 3000 mesh, and 8000 mesh diamond sandpaper (Rong HRTX) on a grinding and polishing machine (Biao Le MiniMet1000). The attachments on the polished surface were blown off with an ear-cleaning bulb, and the surface silicon element distribution was analyzed using EDS element analysis of a scanning electron microscope SU8020 after gold spraying.

[0040] The silicon distribution of T700 carbon fiber precursor is as follows Figure 3 Due to the low resolution, the silicon element distribution cannot be obtained.

[0041] Comparative Example 2

[0042] Since T700 carbon fiber filaments are conductive and strong enough to be self-supporting, the EDS element analysis of the scanning electron microscope SU8020 was directly used to observe the distribution of silicon elements on the cross-sectional surface.

[0043] The silicon element distribution of T700 carbon fiber is as follows Figure 4 Due to the low resolution, the silicon element distribution cannot be obtained.

[0044] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, and without the need to carry out unnecessary experimental conditions, the present invention can be implemented in a wide range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principles of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departure from the disclosed scope in the application, and changes made with conventional techniques known in the art.

Claims

1. A method for characterizing the silicon element distribution of carbon fiber precursor and carbon fiber, comprising the following steps: 1) Embedding the carbon fiber precursor or carbon fiber to be tested in resin to prepare a test sample; 2) After the test sample is sprayed with gold, it is tested using a nano-ion probe to obtain the Si / C value and silicon element distribution diagram of the carbon fiber precursor or carbon filament. The silicon element distribution diagram of the carbon fiber precursor can be used to visually judge whether the oil agent has penetrated into the precursor and whether the oil film formed by the oil agent on the precursor is uniform. The silicon element distribution diagram of the carbon filament can be used to visually judge the residual position of the silicon element in the carbon filament.

2. The method according to claim 1, characterized in that: In step 1), the resin has a Barcol hardness higher than 60, and no volatiles are released under high vacuum conditions.

3. The method according to claim 1, characterized in that: The test sample is prepared by the following method: Araldite 506 resin, curing agent 1 of Araldite 506 resin and curing agent 2 of Araldite 506 resin are uniformly mixed, added into a mold, the carbon fiber precursor or carbon filament to be tested is vertically inserted into the resin mixture, cured, the resin embedded with the carbon fiber precursor or carbon filament to be tested is demolded, and a disc is obtained by low-temperature brittle fracture, grinding and polishing until the brittle fracture surface of the disc is close to a mirror surface, and removing the attachments to obtain the test sample.

4. The method according to claim 3, characterized in that: The curing agent 1 of the Araldite 506 resin is 1,8-diamino-p-menthane; The curing agent 2 of the Araldite 506 resin is 1-(2-aminoethyl)piperazine; Araldite 506 resin, Araldite 506 resin curing agent 1, and Araldite 506 resin curing agent 2 are mixed in a mass ratio of 7.5:6-8:0-2; The shape of the mold is cylindrical, and its diameter is 10-30mm; The curing temperature is 40-50° C. and the curing time is 5-30 hours.

5. The method according to claim 3, characterized in that: The low-temperature brittle fracture is carried out in liquid nitrogen; The disc has a thickness of 2-10 mm and a diameter of 10-30 mm.

6. The method according to claim 3, characterized in that: The grinding and polishing is performed by grinding with sandpapers of different meshes, the meshes of the sandpapers are 200-400, 800-1500, 2500-3000, 5000-8000 from low to high, and the material of the sandpapers is diamond sandpaper.

7. The method according to claim 1, characterized in that: In step 2), the conditions for the nano-ion probe test are: using O - Primary ion current, beam spot diameter 50nm, intensity 50pA, acceleration voltage 16kV.

Citation Information

Patent Citations

  • Carbon fiber and method for producing same

    CN114150402A

  • Preparation method of micron presolar grains transmission electron microscope sample

    CN107941832A

  • Characterization method of pre-oxidized fiber sheath-core structure

    CN111562279A